Relationship between attention shifting and tennis performance during singles matches - Ishihara, T.; Kobayashi, T.; Kuroda, Y.; Mizuno, M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Cognitive ability, such as attention shifting, during tennis matches may be associated with players` performance through physical ability, technique, and exercise intensity. However, examinations of the relationship between attention shifting and performance in sport are limited to laboratory settings. The present study examined the relationships between exercise intensity, attention shifting, and tennis performance in singles tennis matches involving university tennis players using a field-based approach. METHODS: Sixteen university tennis players participated. Participants were evaluated concerning their attention shifting using a local-global task before a singles tennis match (pre-test: 0 minutes), during the match (inter-test: 30 minutes), and after the match (post-test: 60 minutes). Exercise intensity was evaluated using a heart rate monitor and ratings of perceived exertion. RESULTS: Higher ratings of perceived exertion and longer duration of vigorous physical activity were correlated with lower attention shifting at the inter-test period. Higher attention shifting at inter-test was related to greater tennis performance. CONCLUSIONS: The present study suggests that greater attention shifting during a singles tennis match may be related to higher quality tennis performance, and higher exercise intensity and perceived exertion may be associated with impairment of attention shifting during a match. Strategies for maintaining attention shifting during high-intensity physical activity in a tennis singles match may contribute to improved tennis performance.